Chronic thromboembolic pulmonary hypertension and mortality after venous thromboembolism: a nationwide population-based cohort study. (3rd October 2022) - Bonnesen, K; Klok, F A; Andersen, M J; Andersen, A; Nielsen-Kudsk, J E; Mellemkjaer, S; Sorensen, H T; Schmidt, M
Abstract: Background: One of the ultimate long-term complications of venous thromboembolism (VTE) is chronic thromboembolic pulmonary hypertension (CTEPH). CTEPH is a condition defined as an increased mean pulmonary arterial pressure of at least 25 mmHg at rest and abnormal pulmonary artery resistance measured by right heart catheterization. To our knowledge, no study has compared mortality in VTE patients developing CTEPH to those who do not. Purpose: We aimed to investigate the influence of CTEPH on long-term VTE mortality, by examining how receiving any pulmonary hypertension (PH) diagnosis following VTE influenced mortality. Methods: We conducted a population-based cohort study of all adult Danish patients with an incident in or outpatient VTE diagnosis from 1995 through 2016. We excluded patients with a previous PH diagnosis. We defined CTEPH as receiving any PH diagnosis within two years following VTE. We categorized VTE by type (deep venous thrombosis [DVT] or pulmonary embolism [PE]) and provoking risk factors. We followed patients from two years after VTE until the first of death, emigration, or 31 December 2016. We calculated mortality rates and standardized mortality rate ratios (SMRs) of the association between PH and all-cause mortality and cause-specific mortality due to cancer and cardiovascular diseases. We also stratified the analyses by baseline presence of comorbidity (congestive heart failure, chronic pulmonary disease, and/or interstitial pulmonary disease). Results: In 89, 062 VTE patients alive two years after their VTE, 724 developed PH. The mortality rate per 1, 000 person-years was 121 (95% confidence interval [CI]: 110–134) in patients with PH and 48 (95% CI: 47–48) in patients without PH. The SMR was 2.05 (95% CI: 1.77–2.37) for all VTE patients, 2.20 (95% CI: 1.53–3.16) for DVT patients, and 1.72 (95% CI: 1.47–2.01) for PE patients. The SMR was 1.79 (95% CI: 1.28–2.51) in VTE patients with a provoking VTE risk factor and 2.15 (95% CI: 1.83–2.53) in VTE patients without a provoking VTE risk factor. PH was associated with increased cause-specific mortality due to cardiovascular diseases (SMR=2.31, 95% CI: 1.75–3.06), but not cancer (SMR=0.94, 95% CI: 0.64–1.38). The SMR was 2.36 (95% CI: 2.06–2.71) in patients with comorbidity and 1.80 (95% CI: 1.45–2.24) in patients without comorbidity. Conclusion: Development of PH, as a measure of CTEPH, within two years following incident VTE was associated with two-fold increased mortality in two-year VTE survivors. The increase in mortality was driven by cardiovascular causes. Funding Acknowledgement: Type of funding sources: None.